A novel optimized routing algorithm for QoS traffic engineering in SDN-based mobile networks - Amir Alidadi; Saeedreza Arab; Tayebeh Askari (ICT Express, 2022)
Nodes in mobile networks change position randomly and quickly so modify their attachment point to the network. A most suitable method for handoff in core of the network is MPLS. For MPLS-TE, the most critical issue is LSP configuration. The goal of the routing algorithms in MPLS-TE is resource management and satisfy QoS metrics. The promising new SDN architecture can be a useful help to MPLS-TE due to its good features. This paper introduces a novel and low complexity SDN-MPLS algorithm. The proposed algorithm advances bandwidth-restricted routing as it trade-offs between network load balancing, route length, energy-saving with low complexity in mobile networks.